1988
DOI: 10.21000/jasmr88020022
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of a Site Near a Smelter Using Sludge/Flyash Amendments: Herbaceous Species

Abstract: Abstract.--Emissions from two zinc smelters in Carbon County, PA, over an 80-year_ period caused the defoliation of nearby Blue Mountain. High levels of so 2 slowly killed off the existing oak-chestnut forest and particulate metals built to very high levels in the soil. Current metals levels in the soil are as high as t,300 ppm Cd; 6,474 ppm Pb; and 32,085 ppm Zn. These high levels have stopped microbial activity, and there has been no decomposition or regeneration for decades. The site is now on the EPA Super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…For example, emissions of the Zn smelters at Palmerton, PA, have killed or prevent regrowth of natural forests (Beyer, 1988;Buchauer, 1973;Oyler, 1988), and caused Zn toxicity in garden crops, lawn grasses, deer, and grazing horses (Beyer, 1988;Chaneyet aI., 1988). Zinc phytotoxicity to grasses is so severe in the Borough of Palmerton that many homeowners have covered their lawns with stones or other mulch materials.…”
Section: Sources and Significance Of Zn Contaminationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, emissions of the Zn smelters at Palmerton, PA, have killed or prevent regrowth of natural forests (Beyer, 1988;Buchauer, 1973;Oyler, 1988), and caused Zn toxicity in garden crops, lawn grasses, deer, and grazing horses (Beyer, 1988;Chaneyet aI., 1988). Zinc phytotoxicity to grasses is so severe in the Borough of Palmerton that many homeowners have covered their lawns with stones or other mulch materials.…”
Section: Sources and Significance Of Zn Contaminationmentioning
confidence: 99%
“…Bradshaw and colleagues introduced the use of metal tolerant grasses (and minimal fertilization and limestone application) to revegetate these soils (Bradshaw, 1977;Smith and Bradshaw, 1979;Johnson et aI., 1977;Williamson and Johnson, 1981;Oyler, 1988). 'Merlin' red fescue is very effective at providing erosion control at these sites, and this tolerant plant excludes Zn and Cd very effectively (Chaney et aI., 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Elements such as B, Mo, Se, and V tend to be concentrated on the surface of the fly ash particles and leach first, while the remaining elements weather less readily since they are embedded within the silica matrix (Dreesen et al, 1977). Fruchter et al (1990), Oyler (1988) and Warren and Dudas (1984) report studies concerning fly ash weathering and the use of alkaline fly ash as an ameliorant for acid mine drainage. Fruchter et al (1990) found that the leachate concentrations of Al, Fe, Cu, S, Ba, Sr, Cu, and Cr were determined by solubilitycontrolling solids, but geochemical reactions controlling As, B, Cd, Mo, and Se levels were unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…Warren and Dudas (1984) found that when fly ash was leached with dilute sulfuric acid, initial leachate concentrations of Ca, Na, and K were high and subsequent leachings contained higher amounts of Si and Al. Oyler (1988) combined sludge with fly ash, claiming the fly ash alone without incorporation would dry and blow or erode off the plot. His conclusion was that successful revegetation using fly ash/sludge mixtures was possible.…”
Section: Introductionmentioning
confidence: 99%